APPLICATION OF SCHOOL TV MEDIA IN THE CONTEXT OF STRENGTHENING EARLY CHILDHOOD DIGITAL LITERACY IN TK AL AZHAR 13 RAWAMANGUN - Tri Rahayu Budiarti; Siti Agustiani Rubiah; Rini Kurniawati; Sri Watini (Jurnal Scientia, 2022)
The purpose of this study is to apply School TV as a medium in strengthening digital literacy from an early age for early childhood at the Kindergarten (TK) level. The urgency of digital literacy for early childhood is because an understanding of digital literacy will result in the birth of children who are intelligent academically, intelligently, and emotionally and spiritually. Various special educational broadcasts on School TV can be a solution in the process of digital literacy for early childhood by broadcasting educational information so that the process of strengthening digital literacy for children can run effectively, the solution is to use School TV. The research method uses a qualitative method with a descriptive approach with observation and interview data collection techniques involving 7 teachers in kindergarten Azhar 13 Rawamangun. Research results show healthy digital literacy education at the early childhood education level has not been widely implemented. This is the result of teacher interviews with kindergarten teachers Azhar 13 Rawamangunstated that learning about healthy digital literacy specifically had not been carried out so the use of school TV media was an option for schools to implement digital literacy efforts for early childhood as a form of school commitment in the digital era in increasing children's information technology knowledge in learning.